Sex differences in the efficacy of antihypertensive treatment in preventing cardiovascular outcomes and reducing blood pressure: protocol for a systematic review and meta-analysis. Issue 3 (12th March 2020) - Gasbarrino, Karina; Labos, Christopher; Mastropietro, Victoria; Hales, Lindsay; Khan, Nadia; Rabi, Doreen; Daskalopoulou, Stella S
Abstract : Introduction: Hypertension is a leading cause of mortality worldwide and its prevalence is expected to rise over the next decade. Sex differences exist in the epidemiology and pathophysiology of hypertension. It is well established that antihypertensive treatment can significantly reduce the risk for stroke and other cardiovascular disease events. However, it remains unclear whether this effect is dependent on sex. In this protocol, we outlined a systematic review and meta-analysis to evaluate the effects of antihypertensive therapy in (1) reducing blood pressure and (2) preventing cardiovascular morbidity and mortality outcomes for each sex separately. Methods and analysis: The following electronic databases will be searched: Medline, Embase, The Cochrane Library, PubMed, Cumulative Index of Nursing and Allied Health Literature Plus, Web of Science, grey literature (Google Scholar) and several trial registries. Search strategies will be designed to identify human adult (≥18) randomised (and non-randomised) controlled trials, prospective and retrospective cohort studies, and case–control studies concerning 'sex-specific differences associated with the efficacy of antihypertensive treatment'. A preliminary search strategy was developed for Medline (1946—16 September 2019). Two investigators will independently review each article included in the final analysis. Primary outcomes investigated are cardiovascular morbidity and mortality and systolic and diastolic blood pressure. Pooled analyses will be conducted using the random-effects model. Publication bias will be assessed by visual inspection of funnel plots and by Begg's and Egger's statistical tests. Between-studies heterogeneity will be measured using the I 2 test (p<0.10). Sources of heterogeneity will be explored by sensitivity, subgroup and metaregression analyses. Ethics and dissemination: This is the first meta-analysis that will comprehensively compare the efficacy of antihypertensive treatment regimens between men and women. Findings will be shared through scientific conferences and societies, social media and consumer advocacy groups. Results will be used to inform the current guidelines for management of hypertension in men and women by demonstrating the importance of implementing sex-specific recommendations. Ethical considerations are not applicable for this protocol.